Chemical analysis and nutritional assessment of defatted garcinia mangostana seeds used as an addictive on the feed of fish (clarias gariepinus) (2013)
Chemical analysis and nutritional assessment of defatted Garcinia mangostana seeds (DGMS) were undertaken to determine its suitability as an additive at 0.00g, 18.00g, 36.00g, 54.00g and 72.00g inclusion levels in diets and performance of Clarias gariepinus post juveniles. Proximate analysis of DGMS showed that the defatted seeds were high in carbohydrate (71.00 ± 0.79%) but low in protein content (8.10 ± 0.22%). The mineral element analysis detected different minerals with potassium as the highest (270.00ppm). All the fish increased in weight and length significantly (p<0.05) above the initial values though no significant differences were observed among treatments at 49 days in all growth indices showing that the diets were similar in nutritional qualities and adequate for growth of fish